Comparison of neurons derived from mouse P19, rat PC12 and human SH-SY5Y cells in the assessment of chemical- and toxin-induced neurotoxicity - Dina Popova; Jessica Karlsson; Stig O. P. Jacobsson (BMC, 2017)
Abstract Background Exposure to chemicals might be toxic to the developing brain. There is a need for simple and robust in vitro cellular models for evaluation of chemical-induced neurotoxicity as a complement to traditional studies on animals. In this study, neuronally differentiated mouse embryonal carcinoma P19 cells (P19 neurons) were compared with human neuroblastoma SH-SY5Y cells and rat adrenal pheochromocytoma PC12 cells for their ability to detect toxicity of methylmercury (MeHg), okadaic acid and acrylamide. Methods Retinoic acid-treated P19 and SH-SY5Y cells and nerve growth factor-stimulated PC12 cells, allowed to differentiate for 6 days, were exposed to MeHg, okadaic acid and acrylamide for 48 h. Cell survival and neurite outgrowth were assessed with the calcein-AM assay and fluorescence detection of antibodies against the cytoskeletal neuron-specific protein βIII-tubulin, respectively. The effects of glutathione (GSH) and the potent inhibitor of GSH synthesis buthionine sulfoximine (BSO) on the MeHg induced-toxicity were assessed using the PrestoBlue™ cell viability assay and the TMRE mitochondrial membrane potential assay. Results Differentiated P19 cells developed the most extensive neuronal network among the three cell models and were the most sensitive neuronal model to detect neurotoxic effects of the test compounds. MeHg produced a concentration-dependent toxicity in differentiated P19 cells and SH-SY5Y cells, with statistically significant effects at concentrations from 0.1 μM in the P19 neurons and 1 μM in the SH-SY5Y cells. MeHg induced a decrease in the cellular metabolic activity and mitochondrial membrane potential (ΔΨm) in the differentiated P19 cells and SH-SY5Y cells, that were attenuated by GSH. Okadaic acid and acrylamide also showed statistically significant toxicity in the P19 neurons, but not in the SH-SY5Y cells or the P12 cells. Conclusions P19 neurons are more sensitive to detect cytotoxicity of MeHg, okadaic acid and acrylamide than retinoic acid-differentiated SH-SY5Y cells and nerve growth factor-treated PC12 cells. P19 neurons are at least as sensitive as differentiated SH-SY5Y cells to detect the loss of mitochondrial membrane potential produced by MeHg and the protective effects of extracellular GSH on MeHg toxicity. P19 neurons may be a useful model to study neurotoxic effects of chemicals.